A physical model of mantis shrimp for exploring the dynamics of ultrafast systems - Steinhardt, Emma; Hyun, Nak Seung P.; Koh, Je Sung; Freeburn, Gregory; Rosen, Michelle H.; Temel, Fatma Zeynep; Patek, S. N.; Wood, Robert J. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Efficient and effective generation of high-acceleration movement in biology requires a process to control energy flow and amplify mechanical power from power density-limited muscle. Until recently, this ability was exclusive to ultrafast, small organisms, and this process was largely ascribed to the high mechanical power density of small elastic recoil mechanisms. In several ultrafast organisms, linkages suddenly initiate rotation when they overcenter and reverse torque; this process mediates the release of stored elastic energy and enhances the mechanical power output of extremely fast, spring-actuated systems. Here we report the discovery of linkage dynamics and geometric latching that reveals how organisms and synthetic systems generate extremely high-acceleration, short-duration movements. Through synergistic analyses of mantis shrimp strikes, a synthetic mantis shrimp robot, and a dynamic mathematical model, we discover that linkages can exhibit distinct dynamic phases that control energy transfer from stored elastic energy to ultrafast movement. These design principles are embodied in a 1.5-g mantis shrimp scale mechanism capable of striking velocities over 26 m s−1 in air and 5 m s−1 in water. The physical, mathematical, and biological datasets establish latching mechanics with four temporal phases and identify a nondimensional performance metric to analyze potential energy transfer. These temporal phases enable control of an extreme cascade of mechanical power amplification. Linkage dynamics and temporal phase characteristics are easily adjusted through linkage design in robotic and mathematical systems and provide a framework to understand the function of linkages and latches in biological systems.
Keywords: Animals; Biomechanical Phenomena; Crustacea; Energy Transfer; Humans; Models, Biological; Motor Activity; Robotics; Bioinspired mechanisms; Bioinspired robotics; Linkage dynamics; Mantis shrimp; Ultrafast motions